KELAYAKAN TEKNIS DAN KEUANGAN PEMBANGUNAN PERUMAHAN DENGAN PARAMETER GREENSHIP RATING TOOL - Joko Setiono; Taufiq Rochman (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2022)
AbstractThe idea of green building is adopted in residential dwellings to reduce environmental concerns by enhancing the environmental quality that impacts the health of building occupants and the surrounding environment. The application idea of green buildings is to address ecologically friendly features, which may be accomplished utilizing the Greenship Rating Tools evaluation requirements for residential construction. Prior to the building of housing, the most significant feature of this thesis is to conduct a technical and financial feasibility analysis. The Malang Residential Home data utilized in this study will be constructed on a 2-hectare plot with three house types: 48/66, 70/84, and 80/112. The necessary information consisted of a site plan, home design drawings, house technical specifications, and Malang's basic unit pricing for the 2018-2019 fiscal year. The evaluation of technical feasibility will be based on three parameters: BBC, BFC, and GBC. The financial viability will be evaluated using four parameters: NPV, BCR, IRR, and PBP. Additionally, the sensitivity would be examined based on variations in the proportion of capital, as well as an increase or decrease in the project's income and outcome. The research determined the technical feasibility of BBC to be between 60 and 75 percent, BFC to be between 0.60 and 1.0%, and GBC to be greater than 10%. The satisfaction of Parameter Greenship Rating Tools was awarded scores ranging from 3542 to 3542, placing Malang Residential Housing in the silver category. The financial feasibility analysis yielded NPV of IDR 1,382,745,228; BCR of 1.02; IRR of 59.75 percent; and PBP of 1 year and six months. Due to the sensitivity of the project's income and outcome to its viability, it was determined that the project was viableKeywords: green building, technical feasibility, financial feasibility